Research trends and hotspot evolution of exercise-regulated myokines: a bibliometric analysis from 2003 to 2023 - Sun, Zhiyuan; Wu, Zekai; Zhu, Lei; Li, Xinhe; Xu, Dongdong; Tian, Xuewen; Mao, Dewei (Frontiers in Physiology, 2024)
The lack of physical activity is a common issue in modern society and is considered a major risk factor for various chronic non-communicable diseases. Bioactive factors secreted by skeletal muscle during exercise play a crucial role in inter-organ interactions. Since the concept of "myokines" was proposed in 2004, hundreds of regulatory myokines have been identified. Visual analysis of research on exercise-regulated myokines is significant to explore research hotspots and frontiers in this field.Research literature on exercise-regulated myokines from 2003 to 2023 in the "Web of Science" database was used as the data source. Knowledge maps were drawn using "VOS Viewer, CiteSpace, and R-bibliometrix" software.: A total of 1405 papers were included, showing a fluctuating yet slow growth in annual publications. The United States and China led in the number of publications and collaboration networks. Harvard University ranked first with 120 publications. CIBER (centrality 0.16) and the University of California System (centrality 0.16) were pivotal in advancing this field. PEDERSEN BK led author rankings with 41 publications and 1952 citations. FRONTIERS IN PHYSIOLOGYranked first among journals with 64 publications and the highest g-index (39), while PLOS ONE had the highest h-index (25) and most citations (2599). Key co-cited reference clusters included #1 skeletal muscle dysfunction, #2 obesity, #6 ASCs, and #7 adaptive immunocytes. Pontus Boström's paper had a notable citation burst intensity of 77.37. High-frequency keywords were "exercise" (509), "skeletal muscle" (452), and "expression" (293), with long-term keywords such as #0 irisin, #2 insulin resistance, #3 transcription, and #6 physical activity. Recently, keywords like "physical exercise," "resistance exercise," "aerobic exercise," "insulin," and "oxidative stress" have emerged. Conclusion: Research in the field of exercise-regulated myokines shows an overall upward trend.The focus areas include myokines mediated by different types of exercise, the interaction of irisinmediated muscle with other organs, and the important role of myokine-mediated oxidative stress in exercise simulation.